Benserazide is a novel inhibitor targeting PKM2 for melanoma treatment. Issue 1 (13th November 2019) - Zhou, Youyou; Huang, Zunnan; Su, Juan; Li, Jie; Zhao, Shuang; Wu, Lisha; Zhang, JiangLing; He, Yijing; Zhang, Guigui; Tao, Juan; Zhou, Jianda; Chen, Xiang; et al.
Abstract : The M2 splice isoform of pyruvate kinase (PKM2) is a key enzyme for generating pyruvate and ATP in the glycolytic pathway, whereas the role of PKM2 in tumorigenesis remains a subject of debate. In our study, we found PKM2 is highly expressed in melanoma patients and the malignance is positively correlated with high PKM2 activity and glycolytic capability in melanoma cells. Suppression of PKM2 expression by knocking down markedly attenuated malignant phenotype both in vitro and in vivo, and restoration of PKM2 expression in PKM2 depleted cells could rescue melanoma cells proliferation, invasion and metastasis. With the data indicating PKM2 as a potential therapeutic target, we performed screening for PKM2 inhibitors and identified benserazide (Ben), a drug currently in clinical use. We demonstrated that Ben directly binds to and blocks PKM2 enzyme activity, leading to inhibition of aerobic glycolysis concurrent up‐regulation of OXPHOS. Of note, despite PKM2 is very similar to PKM1, Ben does not affect PKM1 enzyme activity. We showed that Ben significantly inhibits cell proliferation, colony formation, invasion and migration in vitro and in vivo . The specificity of Ben was demonstrated by the findings that, suppression of PKM2 expression diminishes the efficacy of Ben in inhibition of melanoma cell growth; ectopic PKM2 expression in normal cells sensitizes cells to Ben treatment. Interestingly, PKM2 activity and aerobic glycolysis are upregulated in BRAFi‐resistant melanoma cells. As a result, BRAFi‐resistant cells exhibit heightened sensitivity to suppression of PKM2 expression or treatment with Ben both in vitro and in vivo . Abstract : What's new? Cancer cells fuel their rapid growth by shifting energy metabolism pathways to aerobic glycolysis, thereby enabling accelerated production of ATP, the energy currency of cells. The pyruvate kinase isoform M2 (PKM2) plays a critical role in catalyzing pyruvate and ATP generation in the final step of glycolysis. This study shows that PKM2 is highly expressed in melanoma and that its activity is correlated with melanoma cell invasion and migration. PKM2 activity was successfully inhibited by the decarboxylase inhibitor benserazide, both in vitro and in vivo . In the process of blocking glycolysis, benserazide also facilitated a return to normal energy metabolism.